2017
DOI: 10.1016/j.marchem.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Controls on dissolved and particulate iron distributions in surface waters of the Western Antarctic Peninsula shelf

Abstract: The Western Antarctic Peninsula (WAP) displays high but variable productivity and is also undergoing rapid change. Long-term studies of phytoplankton communities and primary production have suggested transient limitation by the micronutrient iron (Fe), but to date no data have been available to test this hypothesis. Here, we present the first spatially extensive, multi-year measurements of dissolved and particulate trace metals in surface waters to investigate the key sources and sinks of Fe in the central WAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
104
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(114 citation statements)
references
References 108 publications
6
104
3
1
Order By: Relevance
“…Although many stations had dFe concentrations that hovered around the growth‐limiting level of 0.1 nM (Sedwick et al, ), we observed no evidence of dFe stress in phytoplankton (Arrigo et al, ). Early‐season iron sources in the WAP include sedimentary input from both deep wintertime mixing throughout the water column (Annett et al, ) and horizontal transport from coastlines (Sherrell et al, ), upwelling of Circumpolar Deep Water onto the WAP shelf (Dinniman et al, ; Measures et al, ), sea ice melt (Annett et al, ; Wang et al, ), glacial melt (Annett et al, , ), and precipitation (Annett et al, ). As the season progresses, sea ice melt and warming stratify the water column (Smith et al, ), lifting light limitation but making it more difficult to mix dFe into surface waters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many stations had dFe concentrations that hovered around the growth‐limiting level of 0.1 nM (Sedwick et al, ), we observed no evidence of dFe stress in phytoplankton (Arrigo et al, ). Early‐season iron sources in the WAP include sedimentary input from both deep wintertime mixing throughout the water column (Annett et al, ) and horizontal transport from coastlines (Sherrell et al, ), upwelling of Circumpolar Deep Water onto the WAP shelf (Dinniman et al, ; Measures et al, ), sea ice melt (Annett et al, ; Wang et al, ), glacial melt (Annett et al, , ), and precipitation (Annett et al, ). As the season progresses, sea ice melt and warming stratify the water column (Smith et al, ), lifting light limitation but making it more difficult to mix dFe into surface waters.…”
Section: Discussionmentioning
confidence: 99%
“…As the summer approaches and temperatures increase, ice melt, solar heating, and reduced winds shoal the ML and phytoplankton experience high, and sometimes excessive, light (Alderkamp et al, ). Concurrently, coastal meteoric (glacial meltwater and precipitation) and offshore sea ice melt inputs provide a spatially heterogeneous dFe supply that can continue to fuel some phytoplankton growth (Annett et al, , ). Surface ML light is expected to change in the future as upper ocean circulation, stratification, and sea ice cover continue to undergo rapid and dramatic changes (Martinson et al, ; Meredith et al, ; Moffat & Meredith, ; Schofield et al, ; Stammerjohn et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two different treatments were set: one surface (S) with “surface” water only, and one mix (M) where equal volumes of “surface” and “deep” water were mixed, totaling equivalent 1.0 L volumes in each treatment. Given that no phytoplankton were present in the “deep” water, half of the “surface” water in the S treatments was filtered through an acid‐cleaned, 0.2 μ m filter (Acropak‐200, Pall) inside of a self‐fabricated clean room bubble (Annett et al ) so that all treatments started with the same phytoplankton biomass. For each treatment, three replicates were spiked with 100 μ L of a solution of 17.9 μ mol L −1 Fe 3+ made from an FeCl 3 stock standard diluted into 0.24 mol L −1 ultrapure hydrochloric acid to give a final Fe addition of 1.8 nmol L −1 (“+” treatments, with no significant effects on solution pH), and three bottles were left unaltered as controls.…”
Section: Methodsmentioning
confidence: 99%
“…Seawater samples for iron analysis were collected using the TMC rosette composed of 12 Teflon‐coated Niskin‐X bottles mounted on a polyurethane‐coated aluminum frame that was free of metal anodes and included epoxy encased lead weights (Annett et al ; Sherrell et al ). The rosette was deployed using a plastic‐coated aramid conducting cable through an anodized aluminum sheave.…”
Section: Methodsmentioning
confidence: 99%